Experiment Study of Porous Fiber Material on Infiltration and Runoff of Winter Wheat Farmland in Huaibei Plain, China - Li, Wei; Liu, Shanshan; Qin, Tianling; Xiao, Shangbin; Li, Chenhao; Zhang, Xin; Wang, Kun; Abebe, Sintayehu A. (Frontiers in Earth Science, 2022)
The drought and flood occur frequently in the Huaibei plain, so we conducted the experiments through artificial rainfall, which aimed to explore the effect of porous fiber material (PFM) on farmland runoff and soil water-holding capacity, and reduce risk of the drought and flood disasters. In detail, we designed two rain intensity, four volume of PFM embedding, four growth periods of winter wheat, and a total of 8 experimental groups and 32 rainfall events. The experiments analyzed the change of runoff yield process when PFM was buried in the soil in extreme rainfall events. The result showed that PFM had significantly affected the soil water circulation during the grain-filling period, the start time of runoff was averagely delayed 27.7-42.1 min, compared to other growth periods, and the changing trend of which was similar to peak flow and the water volume of runoff. However, the effect of PFM on runoff yield was slighter in the fallow period. In 100 and 50mm/h, compared to the control groups, PFM decreased the average value of runoff amount by (55.2%~59.6%) and (57.2%~90.2%). Peak flow reduced by (62.2%~68%) and (64.2%~86%). The stable infiltration rate stimulated by the Philip model increased (13.4%~14.3%) and (26.6%~41.3%) on average, respectively. Within 1 hour after the rain, the surface soil water rapidly infiltrated into PFM, which led to the water-storage capacity being higher than the control groups by 0.2~11%Vol. Subsequently, water-holding capacity increased 0.3~2.3%Vol in the 10~70cm depth on average, it had a positive relationship between the volume of PFM embedding and soil water content during the growth period(R2=0.8,0.84). In general, PFM increased infiltration, reduced runoff, and enhanced the water-holding capacity and water-storage capacity, it has good application in long-duration rainfall.